PENGARUH EXECUTIVES NARCISSISM TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR REAL ESTATE DI BURSA EFEK INDONESIA - Sarifa; Mira; Zulaeha, Sitti; Ulandari, Meli (Jurnal Ekonomi Sakti, 2025)
The purpose of this study is to determine the effect of CEO narcissism on tax avoidance moderated by company size in real estate sector companies on the Indonesian Stock Exchange. The population in this study is real estate sector companies listed on the Indonesian Stock Exchange for the period 2021-2023. The sample in this study used a purposive sampling technique, based on the established criteria, a sample of 20 samples was obtained. The type of data used is secondary data in the form of the company's Annual Report. The analysis methods used in this study are: Descriptive Statistics, Classical Assumption Tests, Multiple Linear Regression Analysis with Moderated Regression Analysis and Hypothesis Testing and Using the Eviews 12 Application. The results of this study indicate that CEO narcissism has no effect on tax avoidance, and company size is not able to moderate CEO narcissism on tax avoidance. Keywords: CEO Narcissism, Tax Avoidance, Company Size.